Preharvest culture systems and postharvest factors synergistically improved the antioxidant property of minimally processed corn salad (Valerianella olitoria L.) during cold storage - Lijuan Zhan; Yamin Fan; Emanuela Fontana; Giorgio Tibaldi; Silvana Nicola (Frontiers in Sustainable Food Systems)
To maximize the initial quality going to storage and maintain the postharvest antioxidant property of the minimally processed corn salad, the synergistic effects of culture systems (traditional soil culture system [TCS] vs. soilless culture system [SCS]), washing practices (unwashed vs. washed), packaging methods (flow pack bag [FPB] vs. flow pack tray [FPT]), and storage temperatures (4°C vs. 8°C) on the antioxidant property of minimally processed corn salad (Valerianella olitoria L.) was investigated during 7 days of storage. The results showed that SCS-grown corn salad contained significantly higher levels of total ascorbic acid (TAA) (25.6%), ascorbic acid (AA) (17.5%), total phenols (TP) (57.0%), and antioxidant capacity (AC) (67.0%), but lower levels of chlorophyll and carotenoid than TCS. TAA, AA, and TP were the main contributors to AC, with highly positive correlations between them. Washing practice induced a transient increase in AC value only on processing day (d0). The AC value was significantly higher in SCS-grown leaves than in TCS-grown leaves during the storage period. FPT packaging had a considerable impact on pigments preservation and DHA generation, which was highly culture system-depended. The storage temperature showed no significant influence on overall quality. Browning enzyme (phenylalanine ammonia-lyase [PAL], polyphenol oxidase [PPO], peroxidase [POD]) activities were significantly influenced by factors tested and changed over time. However, no visible browning spots were observed at the end of storage. After 7 days of storage, all leaves were still fresh and marketable with the largest fresh weight loss of 0.38%. Conclusively, the synergism of SCS, washing practice, and FPT favored obtaining high-quality raw material at harvest and maintaining the postharvest antioxidant property of minimally processed corn salad during storage. This unique finding not only offers an innovative and feasible strategy for the fresh-cut industry to produce higher-quality products that meet the growing expectations and demands of modern consumers, but also emphasizes the significance of integrating preharvest and postharvest factors within the fresh supply chain.